Engineering Isoprenoid Biosynthesis in Artemisia annua L. for the Production of Taxadiene: A Key Intermediate of Taxol. (1st February 2015) - Li, Meiya; Jiang, Fusheng; Yu, Xiangli; Miao, Zhiqi
Abstract : Taxadiene is the first committed precursor to paclitaxel, marketed as Taxol, arguably the most important anticancer agent against ovarian and breast cancer. In Taxus, taxadiene is directly synthesized from geranylgeranyl diphosphate (GGPP) that is the common precursor for diterpenoids and is found in most plants and microbes. In this study, Artemisia annua L., a Chinese medicinal herb that grows fast and is rich in terpenoids, was used as a genetic engineering host to produce taxadiene. The TXS (taxadiene synthase) gene, cloned from Taxus and inserted into pCAMBIA1304, was transformed into Artemisia annua L. using the Agrobacterium tumefaciens -mediated method. Thirty independent transgenic plants were obtained, and GC-MS analysis was used to confirm that taxadiene was produced and accumulated up to 129.7  μ g/g dry mass. However, the high expression of TXS did not affect plant growth or photosynthesis in transgenic Artemisia annua L. It is notable that artemisinin is produced and stored in leaves and most taxadiene accumulated in the stem of transgenic Artemisia annua L., suggesting a new way to produce two important compounds in one transgenic plant: leaves for artemisinin and stem for taxadiene. Overall, this study demonstrates that genetic engineering of the taxane biosynthetic pathway in Artemisia annua L. for the production of taxadiene is feasible.